Develompment of an E-Module For Educational Evaluation Course With a Problem Based Learning Framework - Gunawan, Muhammad Ali; Fitri, Amalia; Nelli Murodah (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
The integration of technology into education is important in the current digital era. The aim of this research is to develop an E-module for Educational Evaluation Course using the concept of problem-based learning (PBL). This research uses the ADDIE development model (analysis, design, development, implementation, and evaluation). The research participants were students in the fourth semester of the STAI Ki Ageng Pekalongan Islamic Education Management Study Program. Data collection techniques included documentation, observations, questionnaires, and interviews. The data were analyzed using quantitative and qualitative approaches (mixed methods). The results showed that the development and implementation of e-modules for Educational Evaluation courses have yielded favourable outcomes, showcasing high levels of student learning independence, critical thinking ability, involvement in the learning process, and satisfaction with the e-modules. These results suggest that e-modules serve as effective tools for enhancing student learning experiences and fostering engagement within educational settings, ultimately contributing to improved learning outcomes and heightened student satisfaction. However, the scope of research focusing on a specific course and student demographics may limit the broader applicability of the findings to other educational contexts. Moreover, the predominant reliance on quantitative data analysis may overlook the nuanced aspects of student experiences and perceptions, emphasizing the necessity for more comprehensive qualitative exploration in future investigations.